DISPARITAS PUTUSAN ISBAT NIKAH DALAM PERNIKAHAN YANG MENGGUNAKAN WALI MUHAKKAM : ANALISIS PERBANDINGAN PENETAPAN PENGADILAN AGAMA - Zahra Suryana; Ramdani Wahyu Sururie; Burhanuddin (USRAH: Jurnal Hukum Keluarga Islam, 2026)
The Absence of explicit regulation governing wali muhakkam in Indonesian marriage law has produced inconsistent judicial outcomes in isbat nikah proceedings before Religious Courts. This study analyzes divergent legal reasoning in two comparable cases: Decision No.10/Pdt.P/2023/PA.Wkb (Waikabubak Religious Courts, granted) and Decision No. 49/Pdt.p/2021/PA.Mkm (Mukomuko Religious Courts, rejected), and identifies the factors underlying the disparity between these decisions. This research employs normative juridical methods through library research, with content analysis applied to both decisions, relevant legislation, and legal literature. The findings show that the two judges adopted fundamentally different approaches. The Waikabubak judge applied a contextual approach integrating classical fiqh doctrine, sociological conditions, and the principle of maslahah. Whereas the Mukomuko judge strictly adhered to positive law. Four factors drive this disparity: a legal vacuum and regulatory ambiguity regarding wali muhakkam; differences in the circumstances of the wali nasab and petitioners; divergent judicial paradigms and methods of legal interpretation; and differences in local legal culture and access to justice. This study calls for clearer and more explicit regulation of wali muhakkam to ensure legal certainty and uniformity in Religious Court adjudication